Real-time strategy game using unity3D - Tan, Bronson Jun Kai (Nanyang Technological University, 2020)
This report presents the development progress and results of the creation of a real-time strategy (RTS) game using Unity3D game engine. The game is a cel-shaded monster collecting RTS game – Summon & Fusion, that features players to control and battle with captured monsters in real-time. The project attempts to explore the possibilities of personal development gained by playing an RTS game. The game aims to build a high attachment with players to incentivize players to play via raising the monsters that the players collect. The game employs RGP-style stat-based gameplay and incorporates game mechanics from Multiplayer Online Battle Arenas games such as DotA 2 and Monster Capturing games such as Pokemon. The project uses a game design document to approach the software design of the game and implements the Entity-Component Paradigm approach to the programming of the game. GameObject and Components were developed separately and then wired together to form the game. The game is at a demonstrable stage, consisting of a start state and an end goal with 15 minutes worth of gameplay. Inter-component communication implications experienced by the author as an inexperience developer are then discussed for potential applications to improve the game demo.